cGAS–STING and MyD88 Pathways Synergize in Ly6Chi Monocyte to Promote Streptococcus pneumoniae-Induced Late-Stage Lung IFNγ Production - Patel, Seema; Tucker, Heidi R.; Gogoi, Himanshu; Mansouri, Samira; Jin, Lei (Frontiers in Immunology, 2021)
The cGAS-STING pathway senses DNA and induces type I IFN production. Whether and how the STING pathway crosstalk to other innate immune pathways during pathogen infection, however, remains unclear. Here, we showed that STING was needed for Streptococcus pneumoniae-induced late-, not early-stage of lung IFNγ production. Using knock-out mice, IFNγ reporter mice, intracellular cytokine staining, and adoptive cell transfer, we showed that cGAS-STING-dependent lung IFNγ production was independent of type I IFNs. Furthermore, STING expression in monocyte/monocyte-derived cells governed IFNγ production in the lung via the production of IL-12p70. Surprisingly, DNA stimulation alone could not induce IL-12p70 or IFNγ in Ly6Chi monocyte. The production of IL-12p70, IFNγ required the activation by both DNA and heat-killed S. pneumococcus. Accordingly, MyD88-/- monocyte did not generate IL-12p70 or IFNγ. In summary, the cGAS-STING pathway synergizes with the MyD88 pathway in monocyte to promote late-stage lung IFNγ production during pulmonary pneumococcal infection.